Statement authorised by the Prime Minister to be made to the National Executive of the Labour Party and the General Council of the Trades Union Congress, arising out of the National Council of Labour deputation at 10 Downing Street, on Tuesday, 24th January, 1939
1939-01-25 017b-0001-001 292/946/17b/1(i)